Pengaruh Aplikasi Tandan Kosong Kelapa Sawit Terhadap Produksi Kelapa Sawit - Hasibuan, Syahbudin; Hamdani, Hamdani; Astuti Kuswardani, Retno (Jurnal Penelitian Kelapa Sawit, 2023)
Empty fruit bunch are one of palm oil mills waste. The goal of this study was to see how empty fruit bunch (EFB) treatment affected the yield of fresh fruit bunches in oil palm trees. This was a descriptive study by observing oil palm plantations treated with organic material obtained from research or experiments. The observation was on the production of fresh fruit bunch (FFB). The data obtained came from oil palm plants' production data. Statistical analysis of observation parameters with significant effect was performed using the least significant difference (LSD) test. Any usage of empty fruit bunches composted on oil palm plants which is applied to frond stack increased rachis nutrient level, particularly Ca, Mg, and B, all of which are important in oil palm productivity. In addition, It can also impact N, P, K, Ca, Mg, B, Zn, Cu, even Cl nutrient level on leaf tissues. EFB composting had no significant effect on FFB production. In this study, FFB production was highest with the control treatment, but FFB production with the EFB treatment was slightly lower, not significantly different from the control treatment.